Pengaruh Kepemimpinan Transformasional, Spiritual Leadership, dan Motivasi Pegawai terhadap Efektivitas Kinerja Pegawai - Jermias Prawar; Muhlis Hafel; Herningsih Herningsih (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research analyzes the influence of transformational leadership, spiritual leadership, and motivation on employee performance at the Class IIB Sorong Correctional Institution. This type of research refers to a quantitative approach, using a questionnaire filled out by prison employees as respondents—data analysis techniques using descriptive statistical analysis. Research results show that transformational and spiritual leadership have a significant influence on employee performance, while motivation is also proven to play an important role in increasing performance effectiveness. In conclusion, transformational leadership, spiritual leadership, and motivation have a very significant influence on employee performance. Training that focuses on communication skills, strategic vision, and the ability to motivate teams can increase the effectiveness of transformational leadership. Keywords: Leadership Spiritual, Motivation, Performance, Transformational Leadership